Impact of Veneer Layouts on Plywood Tensile Strength - Jakimovska Popovska, Violeta; Iliev, Borche; Zlateski, Goran (Faculty of Forestry, University of Zagreb, 2017)
The aim of the research presented in this paper is to study the plywood tensile strength through a change of the position of the layers in the structure of the panel around the central axis, without changing the number and the thickness of the veneers. So far it is known that the veneer layouts in plywood structure have significant impact on plywood bending properties. Besides these mechanical properties, the tensile strength of plywood is also a property that can defines the plywood use as structural or non-structural panel. For studying the impact of veneer layouts on plywpood tensile strength, experimental models of nine-layer plywood are made. The models are made from peeled beech veneers with thickness of 1.2, 1.5, 2.2 and 3.2 mm. The modelling is made on the basis of changing the position of veneers with thickness of 3.2 mm around the central axis. Pure water-soluble phenol-formaldehyde resin is used as plywood binder. The tensile strength of the plywood panels was tested in five directions: parallel and perpendicular to the face grain, as well as at the angle of 22.5°, 45° and 67.5° to the face grain of the plywood panel. On the basis of the obtained data for tensile strength in different directions of plywood panel the coefficient of the equality of the tensile strength of the plywood models was calculated (Ket). The coefficient of mass quality (Kmq) was calculated too. The research results showed that the different veneer layouts in plywood structure have significant impact on plywood tensile strength. All tested plywood models meet the defined values of tensile strength in accordance with the requirements of the national (МКС) standard for structural plywood for use in construction. The different layouts of veneer sheets in panel structure gives opportunities for production of panels with different strength characteristics.
Keywords: plywood; veneers; tensile strength; changes; layers